Advancing Gendered Analyses of Entrepreneurship: A Critical Exploration of Entrepreneurial Activity among Gay Men and Lesbian Women. (19th March 2017) - Marlow, Susan; Greene, Francis J.; Coad, Alex
Abstract: This paper advances contemporary gendered analyses of entrepreneurial activity by exploring self‐employment amongst gay men and lesbian women. Within current entrepreneurial debate, heterosexual women have become the visible embodiment of the gendered subject. Our contribution is to queer this assumption when focusing upon the entrepreneurial activity of gays and lesbians. Our core question investigates if 'there is evidence of differences between homosexuals and heterosexuals in their likelihood of being entrepreneurially active'. To address this question, we contrast competing notions of gender stereotypes and discrimination whilst drawing on findings from a large‐scale population‐based study of 163, 000 UK adults. We find few differences between homosexuals and heterosexuals; this persists after examining intersectional patterns and considering if gay and lesbian entrepreneurs choose particular sectors, geographies or forms of self‐employment. As our discussion highlights, the value of this study lies within its critique of contemporary analyses of gender which assume it is an end‐point rather than a foundation for analysing gender as a multiplicity.